MENCIPTAKAN LINGKUNGAN PEMBELAJARAN PAI YANG EFEKTIF - Muhammad Heri Numaeri; Bambang Samsul Arifin (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
Learning strives for students to transform behavior that is not stagnant, this can be seen in changes in students who show a better and positive direction, by Islamic religious teachings to produce good ethical behavior for students. This research is philosophical or literature-based research that is descriptive and analytic, to generalize an effective learning environment in this case leading to Islamic religious education. The learning environment greatly influences the effectiveness of the transformation of knowledge from educators to students, because it contains adequate or inadequate facilities and infrastructure to support the learning process. In Islamic religious learning, educators must correlate and pay attention to the backgrounds of students both in cognition, affection, and the cultures possessed by students, to prevent things that are not coherent with the established national education standards, due to the differentiation of means infrastructure and the number of student ratios, of course, greatly affect the conclusions about the quality produced by students